2021
DOI: 10.1021/acs.biomac.1c00232
|View full text |Cite
|
Sign up to set email alerts
|

Engineered Fluorescent Carbon Dots and G4-G6 PAMAM Dendrimer Nanohybrids for Bioimaging and Gene Delivery

Abstract: Carbon dots (CDs) and G4-G6 (polyamidoamine)­PAMAM-NH2 dendrimers were self-assembled to produce CDs@PAMAM nanohybrids for transfection and bioimaging purposes. CDs were synthesized by the hydrothermal method, using ascorbic acid as a starting precursor and characterized by transmission electron microscopy, UV–Vis, and fluorescence (in solution and solid-state) techniques. CDs were electrostatically combined with PAMAM dendrimers at room temperature, and the UV–Vis, fluorescence, and NMR spectroscopies were us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 74 publications
(117 reference statements)
0
17
0
Order By: Relevance
“…196 In addition to these examples, other organics–CD composites such as (N-(2-aminoethyl)-3-aminopropyl)tris-(2-ethoxy)silane-CDs (KH791-CDs), N-isopropylacrylamide-CDs (NIPAAM-CDs), the CD–RhB core–shell nanocomposite and (polyamidoamine)-PAMAM-NH 2 -CDs have also been reported. 197–200 It is also worth mentioning that the QY of NIPAAM-CDs was as high as 94%. Interestingly, in hydrothermal reactions, the solvents used for work-up could play important roles.…”
Section: Synthesis Of CD Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…196 In addition to these examples, other organics–CD composites such as (N-(2-aminoethyl)-3-aminopropyl)tris-(2-ethoxy)silane-CDs (KH791-CDs), N-isopropylacrylamide-CDs (NIPAAM-CDs), the CD–RhB core–shell nanocomposite and (polyamidoamine)-PAMAM-NH 2 -CDs have also been reported. 197–200 It is also worth mentioning that the QY of NIPAAM-CDs was as high as 94%. Interestingly, in hydrothermal reactions, the solvents used for work-up could play important roles.…”
Section: Synthesis Of CD Compositesmentioning
confidence: 99%
“…12E). 199 Marina and co-workers established a CDs@HNT-DNA model through electrostatic interactions between CDs@HNT and DNA. The results showed that the model did not cause any alteration in the DNA structure and DNA was slowly released through a dialysis membrane in physiological media (Fig.…”
Section: Composites For Biomedical Applicationsmentioning
confidence: 99%
“…Then, PAMAM (aq) and 5.0 mL dichloromethane were added into a stainless-steel autoclave (25 mL) for oil bath; the pH of the solutions was adjusted using HCl solution (0.1 M) or NaOH (0.1 M). The resulting solution was then treated by a one-step hydrothermal method under different conditions, including temperature (60-140 • C), pH (3)(4)(5)(6)(7)(8)(9)(10)(11) and concentrations (0.01-0.1 mM). The pure PDs were obtained by centrifugation and vacuum rotary evaporation, and freeze-dried.…”
Section: Synthesis Of 20g Pamam-dcm Pdsmentioning
confidence: 99%
“…Polyamide-amine (PAMAM) is a highly symmetrical macromolecule with an internal cavity: exhibits good compatibility, unique hydrodynamic properties, and easy modification properties [1][2][3]; receives increasing attention in bioimaging [4,5], sensors [6], catalysis [7,8], drug-delivery [9,10], etc. Previously, Wang and Imae [11] reported that PAMAM, with different terminal groups, including −NH 2 , −C=O, or −OH, could present weak and blue fluorescence.…”
Section: Introductionmentioning
confidence: 99%
“…As literature suggests, the complexation process seems to be dependent on dendrimers physicochemical properties, such as, size, surface charge density, structural morphology or PAMAM generation [40,41]. Moreover, the surface amines exert a crucial role in DNA complexation and cellular internalization, while the tertiary amines can act as buffer to facilitate endosomal escape [40,43]. This image demonstrated that PAMAM G4-PTX dendrimer is not able to complex pDNA and, thus, immobilize it for most of the ratios under investigation.…”
Section: Pdna Complexation: Binary Versus Ternary Systemsmentioning
confidence: 99%